144 Monensin effects on beef calves receiving limited creep-feeding supplementation. (29th July 2019) - de Oliveira, Rhaiza Alves; Vendramini, João; Moriel, Philipe; Arthington, John; Miranda, Miguel; Vedovatto, Marcelo; Silva, Hiran da
Abstract: Monensin is a feed additive used to increase performance of beef cattle; however, the effects on cattle grazing warm-season perennial forages with limited levels of concentrate are inconsistent. The objective of this study was to test the effects of monensin on performance of beef calves receiving limited creep-feeding supplementation. The experiment was conducted in Ona, FL, from April to August (112 d) 2018. The creep-feeding supplementation level was 400 g of soybean meal/d. Calves were supplemented 3 days per week, Monday, Wednesday, and Friday, thus the daily supplementation level was multiplied by 7 d and divided by 3 feeding days. Treatments were monensin (20 g/kg of the expected DMI) or control (no monensin), distributed in a randomized complete block design with four replicates. Twenty four cow-calf pairs (415±29 and 162±35 kg, respectively) were randomly distributed in eight limpograss (Hemarthria altissima) pastures (experimental units; 1.0 ha/pasture; 3 cow-calf pairs/pasture). Pastures were grazed with a continuous and fixed stocking rate. There was no difference in herbage mass (mean = 2, 250 kg/ha, P =0.52, SE = 120) and herbage allowance (HA, mean = 1.2 kg DM/kg LW, P = 0.52, SE = 0.04) between treatments. In addition, there was no effect of monensin on calf average daily gain (mean = 0.77 kg/d, P = 0.27, SE = 0.04), cow body condition score (BCS, mean = 5.1, P = 0.15, SE = 0.15), and calf coccidia infestation (mean = 0.18 log egg count, P = 0.98, SE = 0.08). Calves receiving monensin consumed a lesser (P < 0.01) proportion of the supplement than control in the first 13 h after supplementation (76 vs. 95%). Monensin was not effective to increase performance of beef calves receiving limited creep-feeding supplementation.